1995
DOI: 10.1074/jbc.270.49.29594
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmacytoma Growth Inhibitor Restrictin-P Is an Antagonist of Interleukin 6 and Interleukin 11

Abstract: A stromal protein, designated restrictin-P, that specifically kills plasma-like cells was purified to homogeneity and shown to be identical with activin A. The specificity to plasma-like cells stemmed from the ability of restrictin-P/activin A to competitively antagonize the proliferation-inducing effects of interleukin (IL) 6 and IL-11. Restrictin-P further interfered with the IL-6-induced secretion of acute phase proteins by HepG2 human hepatoma cells and with the IL-6-mediated differentiation of M1 myelobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 58 publications
(41 reference statements)
2
49
2
Order By: Relevance
“…STAT proteins may therefore not be involved in mediating the activin A growth inhibitory signal in this system. Activin A was ®rst studied as an inducer of follicle stimulating hormone (FSH) release (Vale et al, 1986;Ling et al, 1986), and was later found to be a pleiotropic cytokine exhibiting a variety of di erent functions (Murata et al, 1988;Fujimoto et al, 1991;Asashima et al, 1990;Smith et al, 1990;van den Eijnder et al, 1990;Thomsen et al, 1990;Matzuk et al, 1995;Zipori et al, 1986;Brosh et al, 1995). Included among its biological functions are also induction of growth inhibition and cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT proteins may therefore not be involved in mediating the activin A growth inhibitory signal in this system. Activin A was ®rst studied as an inducer of follicle stimulating hormone (FSH) release (Vale et al, 1986;Ling et al, 1986), and was later found to be a pleiotropic cytokine exhibiting a variety of di erent functions (Murata et al, 1988;Fujimoto et al, 1991;Asashima et al, 1990;Smith et al, 1990;van den Eijnder et al, 1990;Thomsen et al, 1990;Matzuk et al, 1995;Zipori et al, 1986;Brosh et al, 1995). Included among its biological functions are also induction of growth inhibition and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…It was further found, using the yeast twohybrid system, that the p21 ras farnesyltransferase (FNTA) a subunit, is bound to the TGFb and activin type I receptors, and is phosphorylated and released intracellularly upon ligand binding (Wang et al, 1996). A common response to activin A signaling is transcriptional activation of the early response gene junB (Hashimoto et al, 1993;Brosh et al, 1995). p21 ras (Whitman and Melton, 1992;Mulder and Morris, 1992) and other components of the MEK, MAPK cascades as well as G proteins (Murthy et al, 1988) have been implicated in a variety of cell systems as targets of TGFb family members.…”
Section: Introductionmentioning
confidence: 99%
“…gp130 binders such as OSM (Sporeno et al, 1994) and neutralizing gp130 mAbs (Hibi et al, 1990;Taga et al, 1992;Saito et al, 1993;Chevalier et al, 1996), as well as soluble forms of gp130 (Narazaki et al, 1993) may be less specific due to their potential interference with the activities of the other members of the IL-6 family of cytokines. Activin A, a stroma-derived antagonist of IL-6 and IL-1 1, may act by interfering with intracellular signaling induced via gp130 (Brosh et al, 1995).…”
Section: Antagonists Of Il-6mentioning
confidence: 99%
“…Activin A, a multifunctional factor of the transforming growth factor-beta (TGF-) superfamily, is mainly produced by microglia and macrophages, and both its anti-inflammatory and pro-inflammatory activities are related to macrophage functions (3)(4)(5)(6). As an anti-inflammatory factor, activin A is involved in regulation of acute phase response in inflammatory diseases via autocrine and paracrine manner, and also acts as an antagonist of interleukin (IL)-6 and IL-11, which can be produced by macrophages (5)(6)(7). Recently our studies have demonstrated that activin A could down-regulate the phagocytosis of lipopolysaccharide (LPS)-activated mouse peritoneal macrophages in vitro and in vivo, which confirms the anti-inflammatory role of activin A (1).…”
Section: Introductionmentioning
confidence: 99%